2012
DOI: 10.1016/j.jhazmat.2012.04.078
|View full text |Cite
|
Sign up to set email alerts
|

De-conjugation behavior of conjugated estrogens in the raw sewage, activated sludge and river water

Abstract: . 2012 De-conjugation behavior of conjugated estrogens in the raw sewage, activated sludge and river water. Journal of Hazardous Materials, 227-228. 49-54. 10.1016Materials, 227-228. 49-54. 10. /j.jhazmat.2012 Contact CEH NORA team at noraceh@ceh.ac.ukThe NERC and CEH trademarks and logos ('the Trademarks') are registered trademarks of NERC in the UK and other countries, and may not be used without the prior written consent of the Trademark owner. The fate and behavior of estrone-3-sulphate (E1-3S), estradio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 21 publications
3
47
0
Order By: Relevance
“…In general, glucuronated estrogens were detected at lower frequencies and concentrations in WWTP influents than the NEs and sulfated estrogens (Liu et al, 2010), partly because the glucuronide forms are more readily deconjugated into free forms in sewage transport pipes where abundant b-glucuronidase is produced by fecal bacteria (Escherichia coli) (D' Ascenzo et al, 2003). Kumar et al (2012) reported a half-life of 0.4 h for both E2-3G and E1-3G, 11.5 h for E2-3S, and 13.9 h for E1-3S in raw sewage in the sewer. Hence, complete absence of glucuronated estrogens in the influent can be expected in the case of a long sewage transport time.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, glucuronated estrogens were detected at lower frequencies and concentrations in WWTP influents than the NEs and sulfated estrogens (Liu et al, 2010), partly because the glucuronide forms are more readily deconjugated into free forms in sewage transport pipes where abundant b-glucuronidase is produced by fecal bacteria (Escherichia coli) (D' Ascenzo et al, 2003). Kumar et al (2012) reported a half-life of 0.4 h for both E2-3G and E1-3G, 11.5 h for E2-3S, and 13.9 h for E1-3S in raw sewage in the sewer. Hence, complete absence of glucuronated estrogens in the influent can be expected in the case of a long sewage transport time.…”
Section: Resultsmentioning
confidence: 99%
“…However, Kumar et al (2012) found that C-NEs were not converted stoichiometrically to their corresponding NEs in raw sewage, so other metabolites may be formed. Additionally, batch studies on the removal of C-NEs usually focused on the concentration variations of the NEs and C-NEs (D'Ascenzo et al, 2003;Gomes et al, 2009;Kumar et al, 2012), while the contributions of enzymatic hydrolysis, biodegradation and sludge adsorption have not yet been separately identified. Thus, the removal pathways of C-NEs in wastewater treatment processes need to be further clarified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the conjugated estrogens are vulnerable in aerobic activated sludge and end up as free estrogens after de-conjugation [62]. The de-conjugation behavior is also observed for pharmaceuticals, resulting in negative removal efficiencies [63,64].…”
Section: Transformation Products (Metabolites) Formed By Human Metabomentioning
confidence: 99%
“…Usually the estrogens are excreted from humans and animals mainly as conjugates of glucuronide or sulphate and a lesser amount as parent compounds in urine and faeces. The conjugates undergo deconjugation to form free estrogens by enzymatic action of bacteria or fungi (Kumar et al, 2012). The occurrence of these hormones in the environment is receiving considerable attention due to the fact that most of these compounds are endocrine disrupting chemicals (Christiansen et al, 2002;Cui et al, 2006;Zheng et al, 2013;Huang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%